2017
DOI: 10.1039/c7ra03231e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanostructured alumina with ultrahigh pore volume for pH-dependent release of curcumin

Abstract: In a new approach, a series of nanoporous non-crystalline alumina (NPA) materials was designed and developed by an evaporation-induced self-assembly method in the presence of various weight ) and large pore sizes (up to 23.0 nm). The results indicated that higher pore volume (2.00 cm 3 g À1 ) was obtained when only tetrabutylammonium bromide (namely NPA-100) was used than when only P123 namely NPA-0 (0.5 cm 3 g À1) was used as a template. These new supports were used, for the first time, as an inorganic host f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 77 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Figure S1 presents the FTIR spectrum of curcumin. The absorption bands at 3510 and 2849 cm –1 may be designated as the O–H vibration and C–H stretching vibration of the OCH 3 unit, respectively . The absorption peak at 1628 cm –1 is due to the stretching vibrations of the CO and CC units .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure S1 presents the FTIR spectrum of curcumin. The absorption bands at 3510 and 2849 cm –1 may be designated as the O–H vibration and C–H stretching vibration of the OCH 3 unit, respectively . The absorption peak at 1628 cm –1 is due to the stretching vibrations of the CO and CC units .…”
Section: Resultsmentioning
confidence: 99%
“…The absorption bands at 3510 and 2849 cm −1 may be designated as the O−H vibration and C−H stretching vibration of the OCH 3 unit, respectively. 42 The absorption peak at 1628 cm −1 is due to the stretching vibrations of the CO and CC units. 43 The other characteristic absorption peaks at 1510, 1430, 1376, and 1283 cm −1 represent the stretching vibrations of the CO group, 43 olefinic C−H bending vibration, 42 the CH 3 bending vibration, 42 and the aromatic enol C−O stretching, 43 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The low-intensity peaks are typically ascribed to the weakly crystalline phase. The formation of the semicrystalline γ-alumina phase is explained by the fact that the complete crystallization temperature of γ-alumina is between 800 and 900 °C while the samples were calcined at 550 °C. , In addition, no obvious peaks are observed for HiPA-CT-8, HiPA-CT-10, and HiPA-CT-12 samples, indicating the amorphous nature of alumina prepared by dicarboxylic acids concomitant with CTAB. It is concluded that the presence of dicarboxylic acid associated with CTAB hinders the crystal growth of γ-alumina due to the interaction of polar head groups of two CTAB molecules with carboxylate groups of dicarboxylic acid molecule and formation of a new template.…”
Section: Resultsmentioning
confidence: 99%
“…Inorganic porous materials with surprising traits such as large surface area and voluminous pores hold great promise for a new generation of adsorbents. Nanoporous alumina (NPA) as a subset of porous materials has been used as an adsorbent due to its peculiar physiochemical properties such as surface with rich hydroxyl groups and Lewis acid sites, ability to attach to various compounds with different functional groups on their surface, high surface-to-volume ratio, low toxicity, and ability to be regenerated. , Antibiotic molecules usually contain −COOH and −NH groups and −Cl or −F atom as another electrostatic point. They could physically or interactively adsorb onto the surface of alumina .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation